Synthesis of a Glycosylphosphatidylinositol (GPI) Fragment as a Potential Substrate for Mannoprotein Transglycosidases - Belz, Tyson F. (Synlett, 2021)
A glycophosphatidylinositol tetrasaccharide fragment was synthesized to mimic the core features of primary model, that of Saccharomyces cerevisiae. The salient feature of this approach is centered on the quick access to various α-1,2- and α-1,6-mannosyl and α-1,4-glycosyl linkages by using simple glycosylation and protective-group techniques. 1D and 2D-J-resolved NMR spectroscopy was used to verify the α-configuration of the new linkages. The tetrasaccharides obtained in this work are useful for examining fungal cell-wall glycoprotein cross-linking by transglycosidase enzymes for antifungal drug development.
Keywords: oligosaccharides; glycosylation; medicinal chemistry